Implementation of Project Based Learning in Teaching Statistics - Rizki Julina; Rahmah Johar; Yuniati Yuniati (Proceedings of AICS - Social Sciences, 2017)
Students have difficulties in learning statistics. For example, students are difficult to solve problem related to reciting data from bar charts, calculate the mean value, and make a pie chart. One of the causes is statistics seldom connected with real-world applications, whereas students should be learning statistics in a real activity-based learning environment. PjBL (Project Based Learning) is a model of learning that integrates new knowledge based on experience in real activity and an in-depth investigation of a real-world topic. The purpose of this study was to describe the students’ project task answers and constraints through the implementation of PjBL. Subjects in this study were 29 students of class IX-5 SMPN 6 Banda Aceh. The data analyzed were students’ project task answers worked in groups and videos. The results showed that 2 of 5 groups could think of useful data that they can gather around them. As they displayed the collected data, all groups chose bar chart. No one group displayed data using pie chart. Furthermore, in interpreting their data, nevertheless 2 of 5 groups could interpret the data well. Moreover, there were students who were less active and less cooperative in the group, however there were students who were usually less active, but they could cooperate in group when researcher implemented the PjBL. When students presented project task, there was student who memorized the project task, so that when he forgot what he must presented, he spontaneously asked his group members what he had not delivered at the presentation. Keywords:learning process, statistics, project based learning.